Catheter Removal versus Retention in the Management of Catheter-Associated Enterococcal Bloodstream Infections - Jonas Marschall; Marilyn L Piccirillo; Victoria J Fraser; Joshua A Doherty; David K Warren; for the CDC Prevention Epicenters Program (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Enterococci are an important cause of central venous catheter (CVC)-associated bloodstream infections (CA-BSI). It is unclear whether CVC removal is necessary to successfully manage enterococcal CA-BSI.